Stories in stone: the enchanted gem carving of Vasily Konovalenko - Nash, Stephen E., author; Hagadorn, James W., author; Muntian, Tatiana, author; Wicker, Richard M., artist; Denver Museum of Nature & Science; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
The first comprehensive treatment of the life of this poorly known Russian artist and the remarkable history of his unique, dynamic, and theatrical sculptures that stand alone in the gem carving world.--Provided by publisher.
Life imitates art, 1957/1973 -- Celebration and persecution, 1973/1981 -- Free at last? Capitalism, New York, and Denver, 1981/1984 -- Crescendos and finales, 1984-1989 -- Unfinished business -- Mineralogical maestro / by James W. Hagadorn -- Konovalenko's and the greater Russian gem carving tradition / by Tatiana Muntian.
With photographs by Richard M. Wicker and contributions from James W. Hagadorn and Tatiana Muntian.
Keywords: Konovalenko, Vasily, 1929-1989; Gem carving -- 20th century; Stone carvers -- Russia -- Biography; Stone carvers -- United States -- Biography